2016
DOI: 10.1680/jmaen.15.00002
|View full text |Cite|
|
Sign up to set email alerts
|

Wave loading on rock lighthouses

Abstract: Historical and contemporary observations of wave-impact loading on rock lighthouses during storms are presented.With climate change potentially causing sea level rise and more energetic wave climates, the longevity of these heritage structures cannot be taken for granted. To obtain a better understanding of the wave-structure interaction, Plymouth University has been working with the General Lighthouse Authorities to develop monitoring and modelling techniques suitable for these isolated masonry structures. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Significant infrastructural impacts included severing of a major railway line at Dawlish (UK), as well as damage to harbors, buildings, and coastal defense works. Out to sea, geophones on the Eddystone lighthouse registered ≈3,000 structure-shaking events during the winter (Raby et al, 2016).…”
Section: Wave Conditions In Winter 2013-2014mentioning
confidence: 99%
“…Significant infrastructural impacts included severing of a major railway line at Dawlish (UK), as well as damage to harbors, buildings, and coastal defense works. Out to sea, geophones on the Eddystone lighthouse registered ≈3,000 structure-shaking events during the winter (Raby et al, 2016).…”
Section: Wave Conditions In Winter 2013-2014mentioning
confidence: 99%
“…Maximum run up, approximately 4 times the water depth h t , occurred for this breaker type. However, this value is lower with respect to the maximum run up observed in the 3D situation of the field during the UK winter storms of 2013/2014 (Raby et al 2015).…”
Section: Large Air Pocketmentioning
confidence: 57%
“…Geophones and cameras were installed on this structure, which is located on a perilous group of rocks some 21 km offshore from Plymouth. The field monitoring showed that the lighthouse can be exposed to different types of breaking waves (Raby et al 2015). Bagnold (1939) was one of the first to perceive that wave loading is affected by the amount of aeration involved during the breaking process.…”
Section: Introductionmentioning
confidence: 99%
“…[1]; [2]; [3]; [4]) but limited observations of structural response have been provided in archive literature. The most notable accounts are by Robert Stevenson on Bell Rock lighthouse ( [4]; [5]) and as reported on a number of previous Eddystone lighthouses ( [1]; [5]). Whilst fascinating to read, at best they provide a patchy understanding of how wave impacts are related to tower motions.…”
Section: Introductionmentioning
confidence: 99%